The role of attitude in sports sponsorship response / Mas Ayu Diana Mohd Fauzi ... [et al.] - Mohd Fauzi, Mas Ayu Diana; Zulqernain, Nurul Syaqirah; Abdull Rahim, Mohd Faisal; Nik Md Salleh, Nik Sarina; Tengku Mohamed, Tengku Nur Azmina (2021)
The important purpose of this study is to identify whether attitude towards sponsorship and attitude towards event will lead to a sports sponsorship response in the 2017 SEA Games. It is important to present the factors that will affect sponsorship response to create a winning situation between the sponsors and sponsees of an event. The high level of sponsorship response among the audience will then arouse the interest of sponsors to support prestigious events such as the SEA Games. Thus, survey questions from previous studies were adopted and customised to collect data. A sample of 100 Malaysian youths from the Kota Bharu district, Kelantan, who have had exposures to sport events was utilised. The results of this study indicate that there is a significant relationship between attitude towards sponsor and consumer response. Attitude towards sponsors in this study is reflected by the perceived sincere feeling towards the sponsors. It is most important for sponsorships to closely monitor sports that have the highest interest among the audience so that they can always give their views to the event organisers to gain a winning situation between both parties. For future research, e-sports sponsorship response will become an interesting area to look into since there is still little research on the factors that contribute to e-sports sponsorship response.